Changes in free amino acids of fermented minced peppers during natural and inoculated fermentation process based on HPLC‐MS/MS. Issue 9 (13th August 2020) - Wang, Yingrui; Zhou, Hui; Ding, Shenghua; Ye, Meiling; Jiang, Liwen; Wang, Rongrong
Abstract : Abstract: Free amino acids (FAAs) participate in the synthesis of quality characteristic ingredients and taste substances in fermented minced peppers (FMPs), and they can be affected by fermentation method and time. In this study, changes in FAAs of FMP during natural fermentation (NF) and inoculated fermentation (IF) process were characterized by HPLC‐MS/MS. The results showed that a total of 20 FAAs were identified, including 8 essential amino acids (AAs), 2 semiessential AAs, and 10 nonessential AAs. Comparing with other FAAs, Gln, Arg, and Asn presented higher content in the whole NF or IF periods. The FAAs content of NF and IF samples showed similar tendency during fermentation process, which first increased and then decreased. The highest content of most FAAs in IF and NF samples was obtained on the 18‐ and 12‐day, respectively. Moreover, the FAA content in IF samples was higher than that in NF ones at the same fermentation time. The taste AAs content accounted for 23.3% to 50.0% in total FAAs, and taste activity value of bitter and umami was higher than sweet and aromatic ones. Based on principal component analysis, comprehensive analysis ranking, and heat map clustering analysis, FMP obtained by IF posed better FAAs quality than NF samples during fermentation process. Practical Application: Free amino acids (FAAs) participate in the synthesis of quality characteristic ingredients and taste substances in fermented minced peppers (FMPs), and they can be affected by fermentation method and time. Changes in FAA varieties and level in FMP during natural fermentation (NF) and inoculated fermentation (IF) process were analyzed using HPLC‐MS/MS. Then, they were performed by principal component analysis (PCA), and clustered with the heat map. The results showed that FMP obtained by IF posed better FAAs quality than NF samples in the whole fermentation. HPLC‐MS/MS was a reliable and effective mean for determining the FAAs and could provide regulation guidelines for improving the quality of FMP during fermentation process.